A Regions of Interest Voxel‐Based Morphometry Study of the Human Brain During High‐Frequency Spinal Cord Stimulation in Patients With Failed Back Surgery Syndrome. Issue 8 (26th June 2020) - De Groote, Sander; Goudman, Lisa; Linderoth, Bengt; Buyck, Félix; Rigoard, Philippe; De Jaeger, Mats; Van Schuerbeek, Peter; Peeters, Ronald; Sunaert, Stefan; Moens, Maarten
Abstract: Introduction: The effectiveness of spinal cord stimulation (SCS) as pain‐relieving treatment for failed back surgery syndrome (FBSS) has already been demonstrated. However, potential structural and functional brain alterations resulting from subsensory SCS are less clear. The aim of this study was to test structural volumetric changes in a priori chosen regions of interest related to chronic pain after 1 month and 3 months of high‐frequency SCS in patients with FBSS. Methods: Eleven patients with FBSS who were scheduled for SCS device implantation were included in this study. All patients underwent a magnetic resonance imaging protocol before SCS device implantation 1 and 3 months after high‐frequency SCS. Pain intensity, pain catastrophizing, and sleep quality were also measured. Regions‐of‐interest voxel‐based morphometry was used to explore grey matter volumetric changes over time. Additionally, volumetric changes were correlated with changes in pain intensity, catastrophizing, and sleep quality. Results: Significant decreases were found in volume in the left and right hippocampus over time. More specifically, a significant difference was revealed between volumes before SCS implantation and after 3 months of SCS. Repeated‐measures correlations revealed a significant positive correlation between volumetric changes in the left hippocampus and changes in back pain score over time and between volumetric changes in the right hippocampus and changes in back pain score over time. Conclusion: In patients with FBSS, high‐frequency SCS influences structural brain regions over time. The volume of the hippocampus was decreased bilaterally after 3 months of high‐frequency SCS with a positive correlation with back pain intensity.